2006
DOI: 10.1603/0022-0493-99.4.1500
|View full text |Cite
|
Sign up to set email alerts
|

Binomial Sequential Sampling Plan for Hemlock Woolly Adelgid (Hemiptera: Adelgidae) Sistens Infesting Individual Eastern Hemlock Trees

Abstract: The hemlock woolly adelgid, Adelges tsugae Annand (Hemiptera: Adelgidae), is an exotic insect pest that is killing eastern hemlock, Tsuga canadensis (L.) Carrière, and Carolina hemlock, Tsuga caroliniana Engelmann, in the eastern United States. We used the sequential interval procedure to develop a binomial sequential sampling plan for A. tsugae sistens on individual eastern hemlock trees that uses nondestructive sampling of new shoots. The actual a (type I) and beta (type II) error rates were essentially 5 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…A different scale could be developed, e.g., the infestation likelihood indicators could be scaled quantitatively as l ow ϭ 0, m edium ϭ 1, and h igh ϭ 2, in which case it would be possible to recalibrate the stopsampling lines on the basis of the new scale. Examples of other scales that have been used in sequential sampling include visual assessment (Meikle et al 2000) and cumulative numbers of infested subsamples (Fidgen et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A different scale could be developed, e.g., the infestation likelihood indicators could be scaled quantitatively as l ow ϭ 0, m edium ϭ 1, and h igh ϭ 2, in which case it would be possible to recalibrate the stopsampling lines on the basis of the new scale. Examples of other scales that have been used in sequential sampling include visual assessment (Meikle et al 2000) and cumulative numbers of infested subsamples (Fidgen et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Costa and Onken (2006) and Fitzpatrick et al (2009) provide methods for early detection and monitoring of infested stands, whereas Fidgen et al (2006) estimated relative levels of infestation for individual trees. In their nondestructive binomial sequential sampling only branches from the lower third of the crown were examined (Fidgen et al 2006). An in situ visual observation of adelgid woolly ovisacs on a certain number of trees can provide an estimate of the general infestation level in an area (Costa andOnken 2006, Faulkenberry et al 2009).…”
Section: Analysis Of Variance and Means ؎ Se For Effect Of T Canadmentioning
confidence: 99%
“…Various sampling protocols including binomial sequential sampling (Fidgen et al 2006) and randomized branch sampling (Evans and Gregoire 2007) have been proposed and tested to assess A. tsugae populations at the individual tree or forest scale (Costa 2005). Randomized branch sampling showed that sistens distribution within the tree crown depended on their population density, suggesting that sampling from the lower regions of the tree alone may not always yield accurate densities (Evans and Gregoire 2007).…”
mentioning
confidence: 99%
“…To quantify A. tsugae infestations, the PSI with the A. tsugae sistens generation was measured pretreatment in 2004 Ð2005 and posttreatment each spring from 2006 to 2008. PSI is based on a binomial sequential sampling plan (Fidgen et al 2006). On each tree, 50 shoots of the most recent growth from the distal ends of each of four branches were examined for the presence or absence of A. tsugae, resulting in 200 shoots examined per tree.…”
Section: Methodsmentioning
confidence: 99%